1993
DOI: 10.1161/01.atv.13.7.1090
|View full text |Cite
|
Sign up to set email alerts
|

Localization and production of plasminogen activator inhibitor-1 in human healthy and atherosclerotic arteries.

Abstract: High plasma levels of plasminogen activator inhibitor type-1 (PAI-1), the principal inhibitor of the fibrinolytic system, have been associated with thrombotic and arterial disease. To study PAI-1 expression in healthy and atherosclerotic human arteries, a detailed analysis was made by light and electron microscopy immunocytochemistry and by in situ hybridization. In healthy arteries PAI-1 was found both at the level of endothelial cells and of smooth muscle cells (SMCs) of the arterial media. In early atherosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
110
0
4

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(124 citation statements)
references
References 21 publications
10
110
0
4
Order By: Relevance
“…Previous studies reported the correlation of PAI‐1 with multiple conventional risk factors of CHD, eg, obesity, glycemic traits, and type 2 diabetes mellitus,6 metabolic syndrome,7 as well as correlation with vessel wall thickness 8. In addition, higher PAI‐1 expression was observed in coronary artery tissues in the presence of atherogenic lesions 9, 10. These findings raise interest in whether PAI‐1 plays a role in early atherosclerosis versus acute thrombosis.…”
Section: Introductionmentioning
confidence: 91%
“…Previous studies reported the correlation of PAI‐1 with multiple conventional risk factors of CHD, eg, obesity, glycemic traits, and type 2 diabetes mellitus,6 metabolic syndrome,7 as well as correlation with vessel wall thickness 8. In addition, higher PAI‐1 expression was observed in coronary artery tissues in the presence of atherogenic lesions 9, 10. These findings raise interest in whether PAI‐1 plays a role in early atherosclerosis versus acute thrombosis.…”
Section: Introductionmentioning
confidence: 91%
“…32 Elevated PAI-1 gene expression, localization, and production have been reported to occur in injured atherosclerotic arteries. 41 In contrast, elevated t-PA activity is associated with a decreased risk of cardiovascular events. 42 Thus, the absence of age-associated impairments in the fibrinolytic system in the physically active women may be mechanistically involved in the lower incidence of atherothrombotic events observed in this population.…”
Section: Fibrinolytic Systemmentioning
confidence: 99%
“…In human aorta, local concentrations of a 2 -AP represented about 10±20% of the concentration found in normal circulating blood (1 mmol/l). In contrast, although plasminogen activators and their inhibitors were elevated in the vessel wall (Schneiderman et al, 1992;Lupu et al, 1993;Padro et al, 1995), they were present only in the nmol/l range (Robbie et al, 1996b). By virtue of its high local concentration and acting as an inhibitor of both plasmin and t-PA, a 2 -AP could have a profound impact on fibrin stability, potentially influencing local plasmin generation as well as plasmin activity.…”
Section: Discussionmentioning
confidence: 94%